2001
DOI: 10.1063/1.1366364
|View full text |Cite
|
Sign up to set email alerts
|

Polymer photonic crystal slab waveguides

Abstract: We present details of the fabrication, calculations, and transmission measurements for finite two-dimensional (2D) polymer photonic crystal (PC) slab waveguides, which were fabricated from a benzocyclobutene polymer on a low refractive index substrate from Teflon. A square air hole lattice (500 nm lattice constant, 300 nm hole diameter) was realized by electron beam lithography and reactive ion etching. Polarization and wavelength dependent transmission results show TE-like and TM-like stop gaps at 1.3 μm exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
37
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 21 publications
2
37
0
Order By: Relevance
“…Polymers themselves only offer moderate refractive indices (n ≈ 1.6) and a less developed nano-structuring fabrication technology compared to silicon. Recently, both PhC structures with a direction independent band gap for transverse electric (TE) polarization in hexagonal lattices [14] as well as EO modulation in PhCs have been demonstrated for polymer based PhC slabs [15][16][17]. However, the light confinement ability and realizable band gaps are small relative to high index materials.…”
Section: Introductionmentioning
confidence: 99%
“…Polymers themselves only offer moderate refractive indices (n ≈ 1.6) and a less developed nano-structuring fabrication technology compared to silicon. Recently, both PhC structures with a direction independent band gap for transverse electric (TE) polarization in hexagonal lattices [14] as well as EO modulation in PhCs have been demonstrated for polymer based PhC slabs [15][16][17]. However, the light confinement ability and realizable band gaps are small relative to high index materials.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoimprinting lithography, which allows a cost-effective and high throughput manufacturing of nanoscale devices, has been envisaged for the filter fabrication. In literature, the devices that are quite similar to the investigated one have been fabricated by e-beam lithography and reactive ion etching, 15 focused ion beam etching, 18 and nanoimprinting lithography. 16,17 We believe that the latter fabrication technique is the most suitable, especially because of its low cost.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Fabry-Perot cavities, made by a couple of two-dimensional (2-D) photonic bandgap mirrors separated by an unperturbed region, have been widely investigated. [9][10][11] Although silicon and III-V semiconductors are the mostly used materials for planar PhCs, [12][13][14] polymer PhC slabs [15][16][17][18][19] are emerging as a valid alternative because of some interesting advantages such as low cost, readiness of functionalization with biochemical receptors, and low optical loss. One of the most promising applications of 2-D PhC cavities is in the field of coarse wavelength division multiplexing (CWDM), which is a well-established technology for short-haul, enterprise, and metro optical networks demanding next-generation chip-scale photonic components having high reliability and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…The previous works, however, have shown that polymer photonic crystal slabs exhibit incomplete in-plane PBGs and they are not suitable for the implementation of waveguides and cavities which play key roles in the PBG functional devices. [11][12][13] In this letter, we show that a polymer slabs suspended in air with a triangular array of air holes can exhibit a complete band gap for transverse electric ͑TE͒-like modes whose magnetic field is parallel to the axis of hole and symmetric to the horizontal plane bisecting the slab. The simulated transmission spectra for the modes propagating along the ⌫K and ⌫M directions of the triangular lattice show a common stop band range which agrees well with the region of the band gap obtained by the photonic band calculation.…”
mentioning
confidence: 99%